Timing of Exposure to High-Concentrates versus High-Quality Forages on Growth and Marbling Deposition in Steers - Brandon M. Koch; Enrique Pavan; John G. Andrae; Susan K. Duckett (Meat and Muscle Biology, 2018)
Forty Angus-cross steers (280 ± 21.4 kg BW, 8 mo.) were used to examine the effects of exposure to 2 diets [high concentrate diets (CONC) versus high quality forages (FOR)] during 2 time periods [early (EARLY; at 30-d post weaning) or late (LATE; just prior to slaughter)] on animal growth, marbling deposition and tenderness. Steers were blocked by weight and randomly assigned to four dietary treatments: 1) CONC-FOR, 2) CONC-CONC, 3) FOR-CONC, or 4) FOR-FOR. Exposure to CONC during the EARLY or LATE period increased (P < 0.05) growth and fat deposition compared to FOR-FOR. Hot carcass weight was greater (P < 0.05) for CONC-CONC and FOR-CONC steers than FOR-FOR and CONC-FOR due to changes in dressing percent. Marbling score was greater (P < 0.05) for CONC-CONC and CONC-FOR compared to FOR-FOR. Exposure to CONC during the EARLY period (CONC-FOR and CONC-CONC) increased (P < 0.05) n-6 polyunsaturated fatty acids (PUFA) deposition in longissimus muscle (LM) and subcutaneous adipose tissue (SQ); whereas, exposure to CONC during the LATE period (CONC-CONC and FOR-CONC) reduced (P < 0.05) n-3 PUFA, trans-11 octadecenoic acid and cis-9 trans-11 isomer of conjugated linoleic acid (CLA). Warner-Bratzler shear force at d 2 and 7 of postmortem aging in ribeye steaks from CONC-CONC and FOR-CONC was greater (P < 0.05) than FOR-FOR and CONC-FOR. Lipogenic gene expression was up-regulated (P < 0.05) and lipolytic gene expression was downregulated (P < 0.06) in SQ from CONC-CONC and FOR-CONC compared to FOR-FOR. Overall, exposure to CONC in both periods increased growth rate and marbling deposition but LATE exposure had the greatest impact on adipose lipogenesis and lipolysis, fatty acid composition, and tenderness.